Taking wrongs seriously. Public perceptions of crime seriousness - O'Connell, Michael (The British journal of criminology, 1996)
This article sets out to investigate three issues central to the study of the public perception of crime seriousness, based on empirical data arising from a survey of a representative sample of Irish (Dublin) citizens. The firstissue is that of the meaning' of seriousness and some evidence is found for the notion that seriousness may be a complex variable reflecting the relative weights given to the wrongfulness and harmfulness of an offence. Secondly, the degree to which perceptions of crime seriousness are consensually held between differing societies, and social groups over time is examined. Finally, the methodological debate over rating and ranking offence seriousness is considered